0672 Twenty-Four Hour Activity Patterns, Pain, and Mental Health Trajectories After a Traumatic Event. (25th May 2022) - Straus, Laura; An, Xinming; Cakmak, Ayse; Clifford, Gari; Neylan, Thomas; McLean, Samuel
Abstract: Introduction: Among those who experience trauma, some individuals develop Adverse Posttraumatic Neuropsychiatric Sequelae (APNS). Identifying biomarkers associated with APNS is critical for predicting trajectories of recovery and informing interventions to reduce the impact of trauma. In this study, we examined objective 24-hour activity patterns and APNS in the weeks following a traumatic event. Methods: Participants (n = 2, 021) were recruited from emergency departments after experiencing trauma. Over 8 weeks, they wore wrist accelerometry devices to measure 24-hour activity patterns, and completed surveys assessing 10 Research Domain Criteria (RDoC) constructs associated with APNS. We aimed to 1) examine the relationship between 24-hour activity patterns and APNS symptoms, and 2) examine how 24-hour activity patterns changed over time in relation to changes in APNS over the 8-week period. A bivariate linear mixed model approach was used to model the cross-sectional and longitudinal associations with each of the 10 RDoC constructs. Results: Overall, participants reporting more pain in the weeks following trauma also showed objectively less 24-hour activity variance (Pearson correlation = -0.14, p = 0.001). An improving pain trajectory over the 8 weeks was associated with increases in daily activity (Pearson correlation = -0.14, p < 0.001) variability in activity (Pearson correlation = -0.12, p < 0.001), and increases in sleep consolidation (Pearson correlation = 0.013, p < 0.001). Within subjects, an increasing number of transitions between sleep and wake over the study period was also associated with worsening self-reported anxiety (Pearson correlation = 0.06, p = 0.003) and sleep problems (Pearson correlation = 0.10, p = 0.003) Conclusion: After a traumatic event, several 24-hour activity biomarkers were associated with APNS. Results suggest pain, activity, and sleep highly influence each other in the weeks following a traumatic event, and 24-hour activity patterns should be considered when making predictions about who is likely to recover from trauma. Targeted interventions for sleep and pain may promote recovery in the other domains. Support (If Any): NIMH U01MH110925, US Army Medical Research and Material Command, the One Mind Foundation, The Mayday Fund, Verily Life Sciences. LDS is supported by a Department of Veterans Affairs Career Development Award (IK2CX002032).